High power millimeter-wave TE03 to TM11 mode converters. Issue 8 (3rd August 2019) - Patel, Amit; Goswami, Riddhi; Mahant, Keyur; Bhatt, Pujita; Mewada, Hiren; Vala, Alpesh; K, Sathyanarayana; Kulkarni, Sanjay
ABSTRACT: Transmission of power from 42 ± 0.2 GHz gyrotron (TE03 mode) to tokamak or dummy load requires a set of transmission line components. It includes a set of mode converters that converts circularly unpolarised TE03 mode to polarised HE11 mode. The mode conversion sequence is methodised in two steps; first from TE03 to TE01 mode and then from TE01 to TM11 mode. The proposed mode converters performance depends on the parameters such as waveguide radius, beat wavelength, number of ripples, its perturbation amplitude (η) and bending angle. These parameters are numerically optimised and verified in CST microwave studio. TE03 to TE01 mode conversion is realised by the generation of intermediate mode TE02 . The mode conversion length for TE03 to TE02 mode converter is6λ0, (where λb is the beat wavelength of corresponding mode conversion) which converts 99.15% of an incident circular TE03 mode power into TE02 mode power. Next, mode converter converts TE02 mode into TE01 mode with 99.06% efficiency along the optimal length of6λb . For TE01 to TM11 mode conversion, two conversion methodologies have been proposed: first using axis arc bend (34.94°) technique to convert TE01 into its analogous degenerate mode with 99.01% conversion efficiency and second using parabolic curve with 90° bend, which gives a conversion efficiency of 97.5%.